Serious games in K-12 education: Benefits and impacts on students with attention, memory and developmental disabilities. Issue 4 (7th November 2017) - Papanastasiou, George; Drigas, Athanasios; Skianis, Charalabos; Lytras, Miltiadis D.
Abstract : Purpose: The purpose of this paper is to explore the integration of serious games (SGs) in the area of special educational needs in the last ten years (2007-2017). Design/methodology/approach: SGs indicate positive effects on students with special educational needs and promote a multi-sensory style of learning. Findings: Research showed that SGs are able to keep K-12 education students with attention, memory and developmental disabilities engaged in classroom facilities scaffolding their learning through increased motivation, independence, autonomy and resultant self-esteem. Research limitations/implications: Time constraints, cost and availability of appropriate games as well as the small sample of the individuals being investigated are some of the research limitations the paper refers to. Practical implications: Learning through SGs has educational values that are based on learning concepts intrinsically motivating. Social implications: Students with attention, memory and developmental disabilities demonstrate characteristics of engagement, creativity, control and communication. Originality/value: SGs-based learning has proven its value added to students with attention, memory and executive control difficulties as well as mental or developmental disabilities engaging students better than when using traditional methods.